Introduction, connection, application, reflection, and extension (ICARE) learning model: The impact on students’ collaboration and communication skills - Siahaan, Parsaoran; Dewi, Ermawati; Suhendi, Endi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
The 21st-Century skills are skills that must be possessed by students to compete in the era of globalization. The provisioning of these skills to students can go through the physics learning process at school. Introduction, Connection, Application, Reflection, and Extension (ICARE) learning model is one of the learning models that can be applied in Physics learning in high school to train students' skills in critical thinking, creative thinking, communication, and collaboration. The purpose of this study was to determine the improvement of communication and collaboration skills of students after applying the ICARE learning model. The research method used was quasi-experimental with a single-group interrupted time series design. The sample were high school students in one of the Karawang districts, consisting of 12 male students and 15 female students. During the learning activities, students will be given a worksheet with several different questions each meeting tailored to the material being studied, and the answer will be used as a source for analyzing their written communication skills. These questions lead students to be able to communicate the results of their experiments following scientific principles. Experimental activities conducted by students will be analyzed to measure their collaborative skills, and students' presentations will be used to measure their oral communication skills. The improvement of those three aspects was analyzed at each meeting. The results showed that the implementation of learning using the ICARE approach was able to improve the ability of students to collaborate with an average score of 7.87 at the first meeting to 15.93 at the second meeting. While the communication, especially report-writing skills of students, increased from the average of1.53 at the first meeting to 3.6 at the second meeting. The aspect of making presentation material increased from 1.67 to 3.17, and the aspect of oral presentation increased from 1.53 to 3.53 at the second meeting. Based on the results obtained, it can be concluded that students' communication and collaboration skills improve after the ICARE learning model implemented